The Nature of the Rights and Obligations of Husband and Wife Couples in Marriage According To Islamic Law, Marriage Law and Compilation of Islamic Law - Cecep Azhar (PT. Global Research Collaboration, 2026)
This research is motivated by the nature of marriage which has an impact on the rights and obligations of husband and wife in marriage. The focus of the aim of this research is to analyze the essence of marriage regarding the rights and obligations of married couples in marriage according to Islamic law, the Marriage Law and the Compilation of Islamic Law. The method used in this research is a systematic literature review based on big data via Schopus publish or perish and Google Scholar publish or perish with VOS viewer visualization. This research is based on a review of research articles published between 2019-2023. Several articles used in the systematic literature review show that marriage has a significant effect on the rights and obligations of married couples in the household. Future researchers are expected to be able to add other variables to the research topic so that they can understand the nature of marriage which influences the rights and obligations of married couples in marriage according to Islamic law, the Marriage Law and the Compilation of Islamic Law.